IMPLEMENTASI SISTEM PENJAMINAN MUTU PENDIDIKAN DALAM MENINGKATKAN KUALITAS DI MAN 2 LEBONG - Alhajj, Irfan Qowwiyul Aziz; Sukarsih; Sihombing, Sri Wahyuni; Gafar Alamsya; Beni Azwar (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2024)
The development of the Educational Quality Assurance System (SPMP) is important to create independence in educational institutions, to foster a culture of quality awareness, to reduce dependency on the government, and begin to focus on meeting the needs of students and society as well as adapting to changes in times, environments, and Science and Technology (IPTEK). This research aims to describe the implementation of SPMP and quality improvement at MAN 2 Lebong. The research method used is qualitative with a descriptive approach. Data analysis techniques include data reduction, presentation, and verification. The results of the research show that: first, the SPMP at MAN 2 Lebong is implemented through 5 cycles, namely (1) Educational Quality Mapping; (2) Planning for Educational Quality Improvement; (3) Implementation of Educational Quality Fulfillment; (4) Monitoring and Evaluation; (5) Establishment of New Standards and Preparation of Quality Improvement Strategies. Second, quality improvement at MAN 2 Lebong refers to the School Work Plan (RKS) that has been prepared and involves all members of the madrasah, coordinated directly by the head of the madrasah along with the madrasah quality development team. Keywords: Quality of Education; Education Quality Assurance System; Islamic Senior High School.   ABSTRAK Pengembangan Sistem Penjaminan Mutu Pendidikan (SPMP) penting untuk menciptakan kemandirian pada lembaga pendidikan, menumbuhkan budaya kesadaran mutu, mengurangi ketergantungan pada pemerintah, serta mulai berfokus pada pemenuhan kebutuhan siswa dan masyarakat serta beradaptasi dengan perubahan zaman, lingkungan, dan Ilmu Pengetahuan dan Teknologi (IPTEK). Penelitian ini bertujuan untuk menggambarkan implementasi SPMP dan peningkatan mutu di MAN 2 Lebong. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan deskriptif. Teknik analisis data meliputi reduksi data, penyajian, dan verifikasi. Hasil penelitian menunjukkan bahwa pertama, SPMP di MAN 2 Lebong diimplementasikan melalui 5 siklus, yaitu (1) Pemetaan Mutu Pendidikan; (2) Perencanaan Peningkatan Mutu Pendidikan; (3) Pelaksanaan Pemenuhan Mutu Pendidikan; (4) Monitoring dan Evaluasi; (5) Penetapan Standar Baru dan Penyusunan Strategi Peningkatan Mutu. Kedua, peningkatan mutu di MAN 2 Lebong mengacu pada Rencana Kerja Sekolah (RKS) yang telah disusun dan melibatkan seluruh anggota madrasah, yang dikoordinasikan langsung oleh kepala madrasah bersama tim pengembangan mutu madrasah. Kata Kunci. Mutu Pendidikan; Sistem Penjaminan Mutu Pendidikan; Madrasah Aliyah.